2016
DOI: 10.1016/j.neucom.2015.11.101
|View full text |Cite
|
Sign up to set email alerts
|

Learning a blind quality evaluation engine of screen content images

Abstract: a b s t r a c tWe in this paper investigate how to blindly predict the visual quality of a screen content image (SCI). With the popularity of multi-client and remote-controlling systems, SCIs and the relevant applications have been a hot research topic. In general, SCIs contain texts or graphics in cartoons, ebooks or captures of computer screens. As for blind quality assessment (QA) of natural scene images (NSIs), it has been well established since NSIs possess certain statistical properties. SCIs however do … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 110 publications
(47 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…Recently, a new strategy has been proposed towards finding the regression module in blind IQA designs [55]. To be more specific, in order to overcome the issue of overfitting, greater than 100,000 images are utilized as training samples to learn the regression module in our blind BIQME metric.…”
Section: B Quality Predictionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a new strategy has been proposed towards finding the regression module in blind IQA designs [55]. To be more specific, in order to overcome the issue of overfitting, greater than 100,000 images are utilized as training samples to learn the regression module in our blind BIQME metric.…”
Section: B Quality Predictionmentioning
confidence: 99%
“…How to label these generated images? In [55], Gu et al indicated that, rather than training on human opinion ratings, using predicted scores computed from high-performance FR-IQA methods as training labels is a good choice. The lately proposed PCQI metric was proven to highly correlate with subjective quality scores on enhancement-relevant databases [35], but it does not take the influence of colorfulness into consideration, which is obviously an important index of image quality.…”
Section: B Quality Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, enhancement technologies may possibly play a more significant role in future IQA research, since they are able to generate betterlooking images, even outperforming the natural images that are deemed to have the optimal quality. At the same time, further research is needed in screen content images, which are becoming particularly important due to their applications in remote computing and cloud gaming [19,14,55].…”
Section: Discussionmentioning
confidence: 99%
“…This means that the weighting cyclopean saliency maps will be replaced by the saliency map derived from either view (left or right) only in equation (18) and (19). Fig.…”
Section: Performance Comparison Between 2d Saliency and "Cyclopean Samentioning
confidence: 99%